2021
DOI: 10.1038/s41421-020-00236-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling of the human decidual immune microenvironment in patients with recurrent pregnancy loss

Abstract: Maintaining homeostasis of the decidual immune microenvironment at the maternal–fetal interface is essential for placentation and reproductive success. Although distinct decidual immune cell subpopulations have been identified under normal conditions, systematic understanding of the spectrum and heterogeneity of leukocytes under recurrent miscarriage in human deciduas remains unclear. To address this, we profiled the respective transcriptomes of 18,646 primary human decidual immune cells isolated from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
135
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 56 publications
(68 reference statements)
14
135
1
Order By: Relevance
“…In order to confirm the robustness of the data, we compared our results with previously published data. We successfully captured all the immune cell populations consistent with previously report (36,38). We also confirmed the variations of immune cells revealed by scRNA-seq data using FACS analysis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In order to confirm the robustness of the data, we compared our results with previously published data. We successfully captured all the immune cell populations consistent with previously report (36,38). We also confirmed the variations of immune cells revealed by scRNA-seq data using FACS analysis.…”
Section: Discussionsupporting
confidence: 84%
“…was diminished in proportion in RPL patients (37,38). However, the global immune variations at the maternal-fetal interface of URPL are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the activated PAMP-PRR system results in the production of IFN, which then acts on local type II pneumocytes, leading to mucus production. Indeed, we found that large amounts of IFNs are produced by AMs following SARS-CoV-2 infection 2 . Intriguingly, the virus can be amplified in AMs depending on their phenotype 2 .…”
Section: Alveoli Are the Battlefieldmentioning
confidence: 77%
“…Indeed, we found that large amounts of IFNs are produced by AMs following SARS-CoV-2 infection 2 . Intriguingly, the virus can be amplified in AMs depending on their phenotype 2 .…”
Section: Alveoli Are the Battlefieldmentioning
confidence: 77%
See 1 more Smart Citation